Aturan Cramer Berbantuan Excel pada Materi Rangkaian Listrik Searah Dua Loop untuk Mengukur Kemampuan Berpikir Komputasi Peserta Didik - Eka Citra Rahayu; Bambang Supriadi; Nila Mutia Dewi (Pendidikan Fisika Universitas Nurul Huda, 2023)
Computational thinking is one of the abilities needed in the 21st century. One of the subjects that requires this ability is physics. One material that is considered difficult is dynamic electrical circuits. The aim of this research is to measure students' computational thinking abilities in solving two-loop electrical circuit problems using Cramer's rules with the help of Microsoft Excel. This research method is included in qualitative descriptive research with a research sample of 10 class XII students at a high school in Banyuwangi. The data collection technique is in the form of student test results in the form of essay questions or descriptions where each question refers to an indicator of computational thinking. The research results showed that 6 people were in the good category for problem decomposition indicators, 8 people were pattern recognition indicators, 7 people were indicators of algorithmic thinking, and 6 people were indicators of abstraction and generalization